Identifying the evidence base of interventions supporting mental health nurses to cope with stressful working environments: A scoping review. (3rd April 2021) - Foster, Alexis; Wood, Emily; Clowes, Mark
Abstract: Aim: To scope the evidence on interventions used to help mental health nurses cope with stressful working environments. Background: Nursing managers may implement interventions to support mental health nurses cope in their role. However, the evidence supporting these interventions has not been recently reviewed. Methods: A scoping review was conducted which entailed searching and selecting potential studies, undertaking data extraction and synthesis. Results: Eighteen studies published since 2000 were identified. They employed different designs, ten used quasi‐experimental methods. Interventions involving active learning appeared beneficial, for example stress reduction courses and mindfulness. However, small sample sizes, short follow‐up periods and variation in outcome measures make it difficult to identify the optimum interventions. No studies have considered cost‐effectiveness. Conclusion: There is some evidence that mental health nurses benefit from interventions to help them cope with stressful working environments. However, higher quality research is needed to establish the effectiveness and cost‐effectiveness of different interventions. Implications for Nursing Management: Managers should provide opportunities and encourage mental health nurses to engage in active learning interventions, for example mindfulness to help them cope with stressful working environments. Nurses also want managers to address organisational issues; however, no research on these types of interventions was identified.